2021
DOI: 10.1007/s11738-021-03295-1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar applications of thidiazuron and putrescine increase leaf iron and chlorophyll concentrations in iron-deficient pot marigold (Calendula officinalis L.)

Abstract: The study was aimed to determine the effects of foliar applications of thidiazuron and putrescine, two compounds that may cause iron (Fe) remobilization, in pot marigold (Calendula officinalis L.) grown in controlled conditions under a limited Fe supply. In a first experiment, plants were grown in a greenhouse in a mixture of sand and perlite with pre-growth/growth Fe concentrations ranging from 0 to 20 µM, and treated three consecutive times with foliar sprays of 0 or 45.4 µM thidiazuron. In a second experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(61 reference statements)
1
0
0
Order By: Relevance
“…Our results showed that (Spd + Spm)/Put ratio continued to increase from days 1 to 7 after Put application, indicating that exogenous Put promoted the transformation of Put to Spd and Spm. Many studies have reported that the (Spd + Spm)/Put ratio was positively correlated with the activity of antioxidant enzymes, and exogenous Put could reduce ROS by enhancing the activities of SOD, POD, and CAT, consistent with the results of this study [58,[60][61][62]. DAO is the key enzyme of the synthesis of GABA by the PAs catabolism pathway.…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that (Spd + Spm)/Put ratio continued to increase from days 1 to 7 after Put application, indicating that exogenous Put promoted the transformation of Put to Spd and Spm. Many studies have reported that the (Spd + Spm)/Put ratio was positively correlated with the activity of antioxidant enzymes, and exogenous Put could reduce ROS by enhancing the activities of SOD, POD, and CAT, consistent with the results of this study [58,[60][61][62]. DAO is the key enzyme of the synthesis of GABA by the PAs catabolism pathway.…”
Section: Discussionsupporting
confidence: 90%